Antioxidant and hepatoprotective activity of vitex honey against paracetamol induced liver damage in mice. Issue 7 (8th July 2015) - Wang, Yuan; Li, Dan; Cheng, Ni; Gao, Hui; Xue, Xiaofeng; Cao, Wei; Sun, Liping
<x xml:space="preserve">Abstract</x> Fourteen vitex honeys from China were investigated to evaluate its antioxidant and hepatoprotective activity against paracetamol-induced liver damage.